Policy Instruments and Infant Feeding for Mothers on Social Assistance: A Comparative Study of Canadian Provinces - Sokolon, Marlene K.; Marier, Patrik (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2023)
Using a modified framework of the social constructions of target populations (SCTP) and Vedung’s typology of policy instruments, this contribution presents a comparative analysis of policy instruments targeting mothers on social assistance to impose “successful” breastfeeding norms in the Canadian provinces. This framework distinguishes between the traditional policy tools of welfare offices and the inclusion of additional oversight by health professionals. The findings expose a variety of policy mixes despite similar commitments to encourage breastfeeding and dissuade the use of infant formula. Most provinces utilize burdened policy instruments for mothers who choose infant formula, such as requiring a medical note. For mothers who breastfeed, most provinces typically deploy beneficial policy instruments such as raising their monthly allowance with little [government] oversight. However, some provinces utilize very different tools which illustrate the diverse health care and social assistance landscape. Québec, for instance, is the only province to provide additional support for women who choose to use formula without medical authorization. In Prince Edward Island, social workers may require a medical note for breastfeeding while in Manitoba there is no additional support for the nutritional needs of breastfeeding mothers.